DEVELOPMENT AND HUMAN SETTLEMENT IN SAGA AND SHIROISHI PLAINS BY RECLAMATION - M. R. Madhav; N. Miura; T. Igarashi (International Association of Lowland Technology, 2002)
The paper describes a case study of development of a very unique region in Japan, consisting of the Ariake bay and the Saga plain, which is subjected to about 6 m of tidal fluctuations and had been reclaimed from the sea over a period of centuries. The sequences of land development, reclamations, developments of water systems, dwellings, etc. are traced. The distinct characteristics of hydrology, irrigation and water management and urban drainage are described. Lastly, the serious problem of subsidence due to excessive pumping of ground water mostly for irrigation but also for industrial and domestic use is high-lighted. The human settlements in this region have evolved along unique patterns of design especially of the water systems and the houses in spite of being subjected to construction on very soft soil, being buffeted by typhoons and subsidence.